Can a University Reproductive Medicine Centre Be Financed Under the Pre-Existing General Conditions in Germany? - Hildebrandt, Thomas; Oversohl, Nicola; Dittrich, Ralf; Lotz, Laura; Beckmann, Matthias W.; Lux, Michael P. (Geburtshilfe und Frauenheilkunde, 2019)
Background Reduced resources for financing healthcare services are available to the German health system. For this reason, demographic development represents one of the greatest challenges for the German health system. Reproductive medicine can offer potential solutions and counteract the ageing of the population through an increase in the birth rate. Most reproductive medical treatments take place in private centres. For the development of new, innovative therapeutic approaches, continuing education and scientific advancement, university centres are essential.Materials and Methods Using multistage contribution margin accounting, IVF and ICSI treatments at the University Fertility Centre Franken (UFF) were investigated in 2012. The cost situation from the perspective of the patient couple and the statutory payer were contrasted with the cost and revenue situation of the service provider as a university reproductive medicine centre.Results The costs for the patient couple for an IVF treatment cycle were 538.71 € and for an ICSI cycle, 700.07 €. For the payer, the costs, including the university flat rate (194.80 €) to be paid, amount to 733.51 € for an IVF cycle and 894.87 € for an ICSI cycle. The payments of the patient couple and the payer were added and this yielded total costs of 1272.22 € and 1594.94 €. The University Fertility Centre Franken, as a part of the Department of Gynaecology of the Erlangen University Hospital, incurred costs of 1364.47 € for an IVF treatment cycle and 1423.48 € for an ICSI treatment cycle. In addition, the OB/GYN clinic had to pay the university hospital a flat general expense rate of 14.9% of the income. There was thus a loss for the department of gynaecology of 281.81 € for an IVF cycle and 66.19 € for an ICSI cycle.Discussion From the perspective of a university reproductive medicine centre, IVF and ICSI treatments currently cannot be performed in a cost-covering manner. At the same time, a reproductive medicine treatment cycle represents a significant financial burden on the patient couple due to only partial cost coverage by most statutory health insurance funds. This therefore demonstrates a need for action in health policy to revise and, in the interest of the patient couples, reproductive medicine centres and, not least of all, in the interest of society, to improve existing cost absorption policies and thus also benefit from this as a society over the long term.Hintergrund Dem deutschen Gesundheitsystem stehen reduzierte Ressourcen zur Finanzierung von Gesundheitsleistungen zur Verfügung. Daher stellt die demografische Entwicklung eine der großen Herausforderungen für das deutsche Gesundheitssystem dar. Die Reproduktionsmedizin kann Lösungsmöglichkeiten bieten und der Überalterung der Gesellschaft durch eine Steigerung der Geburtenziffer entgegenwirken. Die meisten reproduktionsmedizinischen Behandlungen finden in privaten Zentren statt. Für die Entwicklung neuer innovativer Therapieansätze, die Weiterbildung und den wissenschaftlichen Fortschritt sind universitäre Zentren jedoch unerlässlich.Material und Methoden Mithilfe einer mehrstufigen Deckungsbeitragsrechnung wurden im Jahr 2012 sowohl die IVF- als auch ICSI-Behandlungen am Universitäts-Fortpflanzungszentrum Franken (UFF) untersucht. Die Kostensituation aus Sicht des Patientenpaares und der gesetzlichen Kostenträger wurde der Kosten- und Erlössituation des Leistungserbringers als universitäres reproduktionsmedizinisches Zentrum gegenübergestellt.Ergebnisse Die Kosten des Patientenpaares lagen für einen IVF-Behandlungszyklus bei 538,71 € und für einen ICSI-Zyklus bei 700,07 €. Für den Kostenträger beliefen sich die Kosten inklusive der zu entrichtenden Hochschulpauschale (194,80 €) auf 733,51 € für einen IVF-Zyklus bzw. 894,87 € für einen ICSI-Zyklus. Die Zahlungen des Patientenpaares und des Kostenträgers wurden addiert und es ergaben sich Gesamtkosten von 1272,22 € bzw. 1594,94 €. Dem Universitäts-Fortpflanzungszentrum Franken als Bestandteil der Frauenklinik des Universitätsklinikums Erlangen entstanden Kosten von 1364,47 € für einen IVF-Behandlungszyklus und 1423,48 € für einen ICSI-Behandlungszyklus. Zuzüglich musste die Frauenklinik noch eine Gemeinkostenpauschale von 14,9% der Einnahmen an das Universitätsklinikum zahlen. Es ergab sich somit ein Minus für die Frauenklinik von 281,81 € für einen IVF-Zyklus und von 66,19 € für einen ICSI-Zyklus.Diskussion Aus Sicht eines universitären reproduktionsmedizinischen Zentrums sind aktuell IVF- und ICSI-Behandlungen nicht kostendeckend durchführbar. Zugleich stellt ein reproduktionsmedizinischer Behandlungszyklus aufgrund nur partieller Kostenübernahme durch die meisten gesetzlichen Krankenkassen für das Patientenpaar eine erhebliche finanzielle Belastung dar. Es wird somit ein Handlungsbedarf der Gesundheitspolitik aufgezeigt, um bestehende Kostenübernahmegrundsätze zu überarbeiten und im Sinne der Patientenpaare, reproduktionsmedizinischer Zentren und nicht zuletzt im Sinne der Gesellschaft zu verbessern und hiermit langfristig auch als Gesellschaft zu profitieren.
Keywords: IVF; ICSI; reproductive medicine; financial resources; continuing education; endocrinology